The effect of HTLV-1 virulence factors (HBZ, Tax, proviral load), HLA class I and plasma neopterin on manifestation of HTLV-1 associated myelopathy tropical spastic paraparesis - Tarokhian, Hanieh; Taghadosi, Mahdi; Rafatpanah, Hushang; Rajaei, Taraneh; Azarpazhooh, Mahmoud Reza; Valizadeh, Narges; Rezaee, S.A. Rahim (Virus research, 2017)
Previous studies have suggested debatable roles of Tax and HBZ gene expression in the pathogenesis of HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP). In this study, HTLV-1 and host interactions in the manifestation of HAM/TSP were evaluated. A cross-sectional study was conducted on 33 HAM/TSP patients and 38 HTLV-1 asymptomatic carriers (ACs). HTLV-1-Tax, HBZ gene expression, and proviral load (PVL) were assessed using the quantitative real-time PCR (TaqMan), host plasma neopterin level, and HLA-I, and the clinical manifestation were evaluated. The HTLV-1 PVLs in HAM/TSP and ACs were 306±360.741 copies/104 PBMCs and 250.98±629.94 copies/104 PBMCs, respectively; the PVL was higher in HAM/TSP than that in ACs (p=0.004). HTLV-1 Tax and HBZ expression in HAM/TSP was higher than that in ACs, wherein only the Tax expression was statistically significant (p=0.039). In contrast to Japanese HTLV-1-infected subjects, HLA-A*02, HLA-A*24, HLA-Cw*08, and HLA-B*5401 did not exhibit preventive effects for HAM/TSP manifestation. The plasma neopterin level was significantly higher in HAM/TSPs than that in ACs; furthermore, there was a strong significant correlation between plasma neopterin and PVL (R=0.76, p=0.001). Moreover, there were significant correlation between urinary disturbances and haematological indices, including the RBC count (R=−0.61, p=0.01) and Hematocrit (Ht) index (R=−0.75, p=0.002), and between mobility disturbances with Tax expression (R=−0.58, p=0.02) and WBC counts (R=−0.54, p=0.04), and finally, a significant association was found between the sensory disturbances and PVL (p=0.05). Overall, HTLV-1 PVL and Tax may be the valid predictors of disease development, and the neopterin level may be a valid predictor of disease progression. In addition, Tax and neopterin are more helpful than PVL for the monitoring of HTLV-1-infected patients.